Estudio de factibilidad para la creación de una compañía de seguridad privada en la ciudad de Quevedo, año 2013. - Arias Macías, Galo Amador (2015)
In the Ecuador, the levels of delinquency, violence and insecurity are increased in way out control, for what the necessity of creations of new companies arises, seeks to decrease the index of insecurity proportionally, since you would offer a good service of quality with qualified personnel and effective, guided to satisfy the user's necessities. The present investigation was carried out in the City of Quevedo, county of the Ríos whose general objective was to carry out the Study of Feasibility for the creation of a Company of Private Security; which consisted of the following specific objectives: to Carry out the market study that establishes the current situation, offers and it demands of the services lent by the companies of security deprived in the City Quevedo, to Settle down through a technical, economic and financial study the viability and profitability for the creation of a company of private security in the canton Quevedo, to Determine a Plan of Training for the endowment of Human Talent with competitions in the services of security deprived in the City Quevedo. The investigation methods that were used, were the following ones: inductive, deductive, analytic, the techniques that were used were: the direct observation, the survey and the interview. The population's size was determined by means of a direct observation to all the main companies, public and private belonging to the different commercial sectors that demand of the service of private security….